2019
DOI: 10.3390/rel10010044
|View full text |Cite
|
Sign up to set email alerts
|

“Mere” Christian Forgiveness: An Ecumenical Christian Conceptualization of Forgiveness through the Lens of Stress-And-Coping Theory

Abstract: Forgiveness is a central theme within the Christian faith, yet Christian traditions sometimes vary in how they understand and approach the forgiveness process. Nevertheless, in this paper, we present an ecumenical model of Christian forgiveness that highlights the essential components that are shared across most Christian traditions. Importantly, rather than using a theological lens to develop and describe this model, we have primarily used a psychological lens. Specifically, we have adopted stress-and-coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…Christianity highly values forgiveness (Marty, 1998), and the Scriptures and theology (Worthington, 2003; Worthington, Rueger, Davis, & Wortham, 2019) give clear guidance that Christians should forgive both unilaterally and in all cases (Matt. 6:14–15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Christianity highly values forgiveness (Marty, 1998), and the Scriptures and theology (Worthington, 2003; Worthington, Rueger, Davis, & Wortham, 2019) give clear guidance that Christians should forgive both unilaterally and in all cases (Matt. 6:14–15).…”
mentioning
confidence: 99%
“…However, Scripture and theology are less forthcoming about how people are to forgive. One reason is because divine forgiveness is the focus of Christian Scripture and most theologies (Worthington, 2003; Worthington et al, 2019). Divine forgiveness is about God’s judgment and mercy to wrongdoers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although religious scholars can provide important insights about forgiveness, it is also important to examine how religious adherents conceptualize and practice forgiveness. Researchers have advanced scientific understanding of how forgiveness is viewed and practiced by Christians (Macaskill, 2005; Worthington et al, 2019), Jews (Balkin et al, 2009; Heim & Rye, 2003), Muslims (Abu-Raiya & Ayten, 2020; Ayten, 2012), Hindus (Tripathi & Mullet, 2010; Watkins & Regmi, 2004), and Buddhists (Paz et al, 2007). Understanding the similarities and differences in forgiveness across traditions is especially important for clinicians who are seeking to assist clients from a variety of religious backgrounds.…”
Section: Religious Conceptualizations Of Forgivenessmentioning
confidence: 99%
“…For example, Everett Worthington et al have reflected on the Christian notion of forgiveness and have identified four types of forgiveness: divine forgiveness, selfforgiveness, person-to-person forgiveness, and organizational-societal forgiveness. 12 In our discussion on churches and Gukurahundi in Zimbabwe, we embraced all these dimensions of forgiveness. Furthermore, we observed that most participants linked forgiveness to reconciliation.…”
Section: Forgiveness and Reconciliation: An Overviewmentioning
confidence: 99%